2021
DOI: 10.1038/s41598-021-99699-7
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue radiodensity parameters mediate the relationship between self-reported physical activity and lower extremity function in AGES-Reykjavík participants

Abstract: Although previous studies have highlighted the association between physical activity and lower extremity function (LEF) in elderly individuals, the mechanisms underlying this relationship remain debated. Our recent work has recognized the utility of nonlinear trimodal regression analysis (NTRA) parameters in characterizing changes in soft tissue radiodensity as a quantitative construct for sarcopenia in the longitudinal, population-based cohort of the AGES-Reykjavík study. For the present work, we assembled a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Additionally, ML algorithms have been employed in conjunction with the NTRA features to classify cardiac pathophysiologies, Body Mass Index (BMI), and isometric leg strength, achieving classification metrics with accuracy rates exceeding 95% ( Ricciardi et al, 2020a ; Recenti et al, 2020b ; Recenti et al, 2021a ). These features have also mediated the relationship between physical activity and lower extremity function (LEF) in aging individuals ( Edmunds et al, 2021 ). Furthermore, previous studies observed that muscle features exhibit more significant variations compared to fat and connective tissues with regard to age and physical activity levels ( Recenti et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ML algorithms have been employed in conjunction with the NTRA features to classify cardiac pathophysiologies, Body Mass Index (BMI), and isometric leg strength, achieving classification metrics with accuracy rates exceeding 95% ( Ricciardi et al, 2020a ; Recenti et al, 2020b ; Recenti et al, 2021a ). These features have also mediated the relationship between physical activity and lower extremity function (LEF) in aging individuals ( Edmunds et al, 2021 ). Furthermore, previous studies observed that muscle features exhibit more significant variations compared to fat and connective tissues with regard to age and physical activity levels ( Recenti et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%